2020
DOI: 10.3389/fchem.2019.00898
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Tetramer of Galectin-1 and Galectin-3 Amplifies Pro-apoptotic Signaling by Integrating the Activity of Both Galectins

Abstract: Galectin-1 (G1) and galectin-3 (G3) are carbohydrate-binding proteins that can signal apoptosis in T cells. We recently reported that a synthetic tetramer with two G1 and two G3 domains ("G1/G3 Zipper") induces Jurkat T cell death more potently than G1. The pro-apoptotic signaling pathway of G1/G3 Zipper was not elucidated, but we hypothesized based on prior work that the G1 domains acted as the signaling units, while the G3 domains served as anchors that increase glycan-binding affinity. To test this, here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…It is well known that galectin-1 is active as a homodimer, which supports the observed function of the heterotetramer, whereas the minimal functional oligomer of Gal3 was unknown. Here, we showed that the minimum valency for Gal3 activity is also 2, consistent with a report showing that both galectin-1 and Gal3 contribute to the signaling activity of the heterotetramer (37). In contrast to the heterotetramer design, here the Gal3 domains were fused to one terminus of a parallel, α-helical coiled-coil while sfGFP was fused to the other.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is well known that galectin-1 is active as a homodimer, which supports the observed function of the heterotetramer, whereas the minimal functional oligomer of Gal3 was unknown. Here, we showed that the minimum valency for Gal3 activity is also 2, consistent with a report showing that both galectin-1 and Gal3 contribute to the signaling activity of the heterotetramer (37). In contrast to the heterotetramer design, here the Gal3 domains were fused to one terminus of a parallel, α-helical coiled-coil while sfGFP was fused to the other.…”
Section: Discussionsupporting
confidence: 90%
“…It is valuable to understand the biological mechanisms and outcomes of these promiscuous Gal3receptor interactions for pharmaceutical applications or drug discovery (e.g., design of selective Gal3 inhibitors or biomimetic Gal3 agonists). In addition to the Jurkat T cell line, two different receptor-deficient lymphocyte cell lines, J45.01 (CD45 − /CD7 + ) and HuT 78 (CD45 + /CD7 − ), have been used previously to characterize the role of CD45 and CD7 in wild-type Gal3-mediated membrane glycan clustering and cell death signaling (36,37). Unlike J45.01 and HuT 78 T cells, Jurkat T cells express both CD45 and CD7, which differ both in size and availability on the cell surface (Fig.…”
Section: Biochemistrymentioning
confidence: 99%
“…Presenting Gal-1 into a tandem-repeat type with an 8S-linker ((Gal-1) 2 [8S]) maintained its crosslinking activity with laminin and α-DG peptide 4, but attenuated transbridging with core M1 glycopeptides (5--11) was observed. Interestingly, a noticeable increase in trans-bridging towards LacNAc-terminated (12)(13)(14)(15)(16)(17)(18)26) and sialyl-LacNAc-terminated (19)(20)(21)(22)(23)(24)(25)(27)(28)(29) was demonstrated by (Gal-1) 2 [8S] which is attributed to the high affinity of this Gal-1 variant to the ligands compared to Gal-1WT (Figure 6). This difference in crosslinking activity is associated with the Gal-8 linker, 33 aa (8S), between the two Gal-1 monomers providing Gal-8like properties to Gal-1.…”
Section: Presenting Variants ((Gal-1) 2 [8s] Gal-1[8s]gal-3 Gal-3[8s]...mentioning
confidence: 99%
“…[12] Furthermore, a heterotetramer galectin variant with two Gal-1 and Gal-3 domains (G1/G3 Zipper) exhibited a higher apoptotic activity than wild-type Gal-1 and Gal-3 alone or in combination; thus, it can be a good therapeutic candidate for regulating innate and adaptive immunity. [20,21] Dystroglycan (DG) is a transmembrane protein that links the extracellular matrix and intracellular cytoskeleton via α-DG and β-DG, respectively. [22] α-DG is highly O-Mannosylated (O-Man); this plays an important role in its ability to bind basement membrane proteins containing laminin G domains (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation